Auricular Neuromodulation for Mass Vagus Nerve Stimulation: Insights From SOS COVID-19 a Multicentric, Randomized, Controlled, Double-Blind French Pilot Study - Rangon, Claire-Marie; Barruet, Régine; Mazouni, Abdelmadjid; Le Cossec, Chloé; Thevenin, Sophie; Guillaume, Jessica; Léguillier, Teddy; Huysman, Fabienne; Luis, David (Frontiers in Physiology, 2021)
Importance: An exacerbated inflammatory response to SARS-CoV-2 infection is believed to be one of the major causes of COVID-19 disease morbidity and mortality. Neuromodulation therapy, based on vagus nerve stimulation, was recently hypothesized to control both the SARS-CoV-2 replication and the ensuing inflammation likely through inhibition of the Nuclear Factor Kappa-light-chain-enhancer of activated B cells pathway and could, as adjunct treatment, improve clinical outcomes. We propose to test it by stimulation of the auricular branch of the vagus nerve (auricular neuromodulation, AN), a non-invasive procedure through insertion of semi-permanent needles on the ears. Objective: To assess the effect of auricular neuromodulation on clinical outcomes in patients affected by COVID-19. Design, setting, and participants: A multicenter, randomized, placebo-controlled, double-blind clinical trial included 31 patients with COVID-19 respiratory failure requiring hospitalization. Within 72 hours after admission, patients received either AN (n=14) or sham neuromodulation (SN, n=15) in addition to the conventional treatments. Main outcome and Measures: The primary study endpoint was the rate of clinical benefit conferred by AN at D14 as assessed by a 7-point Clinical Progression Scale. The secondary study endpoint was the impact of AN on the rates of ICU transfer and survival at D14. Results: The AN procedure was well tolerated without any reported side effect but with no significant improvement for the measures of both primary (p > 0,3) and secondary (p > 0,05) endpoints at interim analysis. None of the AN patient died but one in SN group (81 years). Two AN patient (73 and 79 years) and one SN patient (59 years) were transferred to ICU. Remarkably, AN patients were older with more representation by males than in the SN arm (median age 75 vs 65 years, 79% male vs 47%). Conclusion: The AN procedure, used within 72 hours after COVID-19 patients’ admission, was safe and could be successfully implemented during the first two waves of COVID-19 in France. Nevertheless, AN did not significantly improve patients’ outcome in our small preliminary study. It is pertinent to explore further in order to validate AN as the non- invasive mass vagal stimulation solution for the next pandemics.